Karakterisasi Permukaan pada Aluminium Anodized dengan Variasi Waktu Menggunakan Pewarna - Aprilia Melisa; Gifran Noval Rahmadoni; Rahmatul Husna; Sarah Rodiatul (Indonesian Journal of Chemical Connections, 2023)
This study investigates the surface characterization of anodized aluminium using natural dyes. Aluminium anodizing is an electrochemical process that produces a thick oxide layer on the aluminium surface. This layer can be coloured using various dyes. The purpose of this research is to analyze the effect of anodizing time on surface characteristics when using natural dyes such as turmeric. The results show that anodizing time significantly affects surface morphology and colour absorption.